2021
DOI: 10.1093/jpepsy/jsab129
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes Among Parents of Children With a Chronic Disease During the COVID-19 Pandemic: The Role of Parental Burn-Out

Abstract: Objective The COVID-19 pandemic and associated quarantine measures highly impacted parental psychological well-being. Parents of children with chronic diseases might be specifically vulnerable as they already face multiple challenges to provide adequate care for their child. The research questions of the current study were twofold: (a) to examine whether parents of children with a chronic disease experienced more anxiety and depression compared to parents of healthy children and (b) to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 33 publications
0
31
1
5
Order By: Relevance
“…Other studies reported similar findings [ 35 , 37 40 ]. This is not surprising, given that comorbidities represent a risk factor for more severe covid-19 presentations [ 41 ] and might be associated with higher levels of distress in both children and parents of those children [ 42 ], and more strict social distancing [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported similar findings [ 35 , 37 40 ]. This is not surprising, given that comorbidities represent a risk factor for more severe covid-19 presentations [ 41 ] and might be associated with higher levels of distress in both children and parents of those children [ 42 ], and more strict social distancing [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… Wauters et al (2022 ) assessed multiple categories of risk that may have contributed to parent mental health during the COVID-19 pandemic. Of those explored, parental burn-out and financial worries correlated most strongly with parental psychological functioning.…”
Section: Assessing Risk Factorsmentioning
confidence: 99%
“…Although researchers have addressed the tremendous impact of the COVID-19 pandemic on parent and child mental health (e.g., Feinberg et al, 2022 ; Russell et al, 2020 ), fewer efforts have focused specifically on parents of children with chronic medical conditions, who are generally at higher risk for psychological distress. Wauters et al (2022 ) aimed to address this gap in the literature by surveying a broad sample of parents from pediatric clinics in Belgium during the early months of the COVID-19 pandemic.…”
mentioning
confidence: 99%
See 2 more Smart Citations